Dual Identity Mantan Teroris Indonesia - Dhestina Religia Mujahid (PALAPA, 2023)
Terrorists have a limited sense of national identity. They wish to replace Pancasila ideology with one founded on the Qur'an and hadith. Thus, what about the former terrorist's identity? Former terrorist actors have renounced violence and terror to fight for an ideology (disengagement). However, not all former terrorists declared themselves members of the Unitary State of the Republic of Indonesia. The purpose of this study is to describe the dual identities of former terrorists who have sworn allegiance to the Unitary State of the Republic of Indonesia. This study employed a qualitative method with a case study approach in ex-terrorist Indonesia. Data were collected using interviews, observation, and documentation, and analyzed according to the Yin case study perspective with the help of Atlas.ti software. This article demonstrates the dual identity of former Indonesian terrorists. All informants have sworn allegiance to the Unitary State of the Republic of Indonesia. This demonstrates an increase in the national identity of rehabilitated terrorist actors, despite several informants having superordinate national identities. Other findings indicated a subordinate identity, namely the identity of a mujahideen. This identity persists, although the permit has been revoked. Informants continued to wish to establish a caliphate state (including Indonesia), even though they no longer desired violence and terror. Hopefully this research can be used in the deradicalization of terrorist actors in Indonesia.